If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -36x + 5 = 0 Reorder the terms: 5 + 8x + -36x = 0 Combine like terms: 8x + -36x = -28x 5 + -28x = 0 Solving 5 + -28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -28x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -28x = 0 + -5 -28x = 0 + -5 Combine like terms: 0 + -5 = -5 -28x = -5 Divide each side by '-28'. x = 0.1785714286 Simplifying x = 0.1785714286
| -4*y+2=10 | | 4.2+x-1.4=75 | | x-5=10.5 | | -4*7+2=10 | | 2(3-2x)=-14 | | x+10x+25(43-2x)=373 | | 8x-y=42 | | Y^2-8X+2+X^2-2y=5 | | 9x^2-100y^4=0 | | -7(1+8v)=29 | | .75x+3=.25x+6 | | 5y+9-y=5+3y-3 | | 16t=80 | | 5x+3-2(x+1)=8x+3 | | (2x^2-5x)(12x^2-5x-2)=0 | | 2(3*x-8)=4(x+1) | | 4x-10+x+80=180 | | 32=-3f+5f | | 3n+12=3n+2 | | 3(x+3)=8x+5-5x+4 | | 8x-2y=42 | | 8x+6+7x+5=56 | | 2x^2+9x=6x+9 | | x+1=y+.6 | | 5y+9-10y=5+3y-3 | | 2x-y(2x+1)=3 | | -2x-107=133+6x | | (4-9i)(7-9i)= | | 14k+13=20 | | 4(c-2)=3(x-3) | | 4k+13=13 | | -133-2x=119-11x |